2017
DOI: 10.4081/ija.2017.993
|View full text |Cite
|
Sign up to set email alerts
|

Yield and qualitative characterisation of seeds of Amaranthus hypochondriacus L. and Amaranthus cruentus L. grown in central Italy

Abstract: Amaranth can be considered a very interesting crop for the Mediterranean region, thanks to its inherent tolerance to disadvantageous growing conditions, along with the high nutritional and nutraceutical value of its seeds. The study aims to evaluate the seed yield, and the oil content and quality of two amaranth genotypes (species Amaranthus hypochondriacus L. and Amaranthus cruentus L., respectively) grown in central Italy, testing two types of soil (loamy and sandy soil). The two species showed a good perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
19
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 49 publications
9
19
3
Order By: Relevance
“…Yields of tested accessions resulted higher than the data of El Gendy et al [42] but in agreement with those reported by Casini and La Rocca [40]. Moreover, compared to results obtained on A. cruentus in the same cultivation environment, but with different accessions [43], all the accessions tested showed slightly higher or comparable yields, except for PI 628793 (Zaire), which gave lower grain yield.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Yields of tested accessions resulted higher than the data of El Gendy et al [42] but in agreement with those reported by Casini and La Rocca [40]. Moreover, compared to results obtained on A. cruentus in the same cultivation environment, but with different accessions [43], all the accessions tested showed slightly higher or comparable yields, except for PI 628793 (Zaire), which gave lower grain yield.…”
Section: Discussionsupporting
confidence: 89%
“…The oil content of the eight amaranth accessions resulted within the range reported by Grobelnik Mlakar et al [19] (5.6-8.1%) and within the range observed by He et al [48] in a study conducted in Wuhan (China) with 7 genotypes of A. cruentus (5.57-7.41%) with different origin (Nigera, Mexico, Czechoslovakia, USA, USA, China and China). On the other hand, our values are higher than those (1.9-5.0%) observed by He et al [49] in a second study involving 7 genotypes of A. cruentus with a different origin (Ghana, Taiwan Sudan, Peru, Guatemala, USA, India) and cultivated in Wuhan (China) and by El Gendy et al [42].…”
Section: Discussioncontrasting
confidence: 73%
“…In our work the molar ratio of saturated and unsaturated fatty acids was established ~ 27:73 among the four amaranth seed oils. Comparable results (23.7:76.3 and 22:78, respectively) were demonstrated in A. hypochondriacus and A. cruentus (El Gendy et al 2018). High percentage of squalene and unsaturated fatty acids in amaranth oil makes it possible for use in medicine.…”
Section: Resultsmentioning
confidence: 79%
“…The genus Amaranthus comprises several species of the Amaranthaceae family whose leaves and seeds are regularly consumed as food by populations in several countries [1,2] among which Brazil is not yet included. The amaranth (Amaranthus spp) is a granífera adapted to produce in regions with high insolation and high temperature [3], conditions of saline stress [4] and hydric [5] and adapts also to altitudes that go from the level of the sea up to 3,500 m [6].…”
Section: Introductionmentioning
confidence: 99%